A novel case of unilateral blepharophimosis syndrome and mental retardation associated with de novo trisomy for chromosome 3q. Issue 9 (September 1997) - Cai, T; Tagle, D A; Xia, X; Yu, P; He, X X; Li, L Y; Xia, J H
Abstract : We have evaluated a 3 2/12 year old girl who presented with unilateral blepharophimosis, ptosis of the eyelid, and mental retardation. Additional dysmorphic features include microcephaly, high, narrow forehead, short stubby fingers, and adduction of the right first toe. Cytogenetic analysis showed an unbalanced karyotype consisting of 46, XX, add(7)(q+) that was de novo in origin. Fluorescence in situ hybridisation (FISH) using microdissected library probe pools from chromosomes 1, 2, 3, 7, and 3q26-qter showed that the additional material on 7q was derived from the distal end of the long arm of chromosome 3. Our results indicate that the patient had an unbalanced translocation, 46, XX, der(7)t(3;7)(q26-qter;q+) which resulted in trisomy for distal 3q. All currently reported cases of BPES (blepharophimosis-ptosis-epicanthus inversus syndrome) with associated cytogenetic abnormalities show interstitial deletions or balanced translocations involving 3q22-q23 or 3p25.3. Our patient shares similar features to BPES, except for the unilateral ptosis and absence of epicanthus inversus. It is possible that our patient has a contiguous gene defect including at least one locus for a type of blepharophimosis, further suggesting that multiple loci exist for eyelid development.